Aktivitas Antimikroorganisme Ekstrak Metanol Daun Gamal (Gliricidia Sepium) Terhadap Neisseria gonorrhoeae Dan Candida albicans - Maria Paolina Grazzia; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2021)
Infectious diseases of the genital tract and the increasing resistance of microorganisms to antibiotic therapy have received high attention in worldwide. Gamal plant (Gliricidia sepium) is a multipurpose leguminous plant that contains various antimicrobial secondary metabolites. This study aims to prove that the methanol extract of gamal leaves can significantly inhibit the growth of the bacteria Neisseria gonorrhoeae and the fungus Candida albicans. The study was carried out in an experimental randomized block design with each treatment repeated 5 times. Types of microorganisms, namely N. gonorrhoeae bacteria and C. albicans fungi as a group and concentrations of methanol extract of gamal leaves (0, 25, 50, 100, 150 and 200 mg/ml and chloramphenicol) as treatments. The results showed that gamal leaf extract could inhibit the growth of the bacteria N. gonorrhoeae and the fungus C. albicans. The inhibition of methanol extract against bacteria and fungi increased with increasing test concentration. This study also showed that the inhibition of methanolic extract of gamal leaves against the fungus C. albicans was higher than N. gonorrhoeae bacteria. The results of the study concluded that the methanol extract of gamal leaves was showed to inhibit the growth of N. gonorrhoeae bacteria and C. albicans bacteria. Gamal leaf methanol extract has the potential to be used as an alternative therapy for infectious diseases of the genital tract, especially vaginal candidiasis and gonorrhea. Keywords: gamal leaves, antimicroorganism, Neisseria gonorrhoeae, Candida albicans